OPTIMALISASI ECENG GONDOK (EICCHORNIA CRASSIPES) SEBAGAI PUPUK ORGANIK CAIR UNTUK PERTANIAN BERKELANJUTAN DAN RAMAH LINGKUNGAN - Retnowati, Dewi; Dewi, Rini Kartika (jurnal ATMOSPHERE, 2025)
Fertilizer is one of the commodities that can increase plant productivity by adding macro and micro element supplements so that agricultural and plantation products have good quality and quantity. Water hyacinth (Eichornia Crassipes) is a plant that is very adaptable to poor environmental conditions, water hyacinth is easy to find and grows quickly even in waters with low nutrient levels. The implementation of this research is in the Basic Chemistry Laboratory of Chemical Engineering, Faculty of Industrial Technology, Malang National Institute of Technology. This research covers a series of processes starting from the preparation of tools and materials, including the collection of main raw materials such as water hyacinth and nutrients including bean sprouts, banana peels, rice washing water and coconut water, variables, processing stages, fermentation. the variables used are the control variables of 1500 grams of water hyacinth. EM4 bioactivator 250 ml, molasses 500 ml, water 2250 ml, pH 4-9, Temperature 38-45 oC and variable changes fermentation time 14 days, 21 days, 28 days, 35 days, Nutrients rice washing water 500 ml, banana peel 500 grams, coconut water 500 ml, bean sprouts 500 grams. The pH produced an average of 4.0 and a temperature of 27-28 oC NPK nutrients with nutrients Coconut water produces the highest nitrogen of 0.36% on the 35th day, rice washing water produces the highest phosphorus of 0.1239% on the 28th day and banana peel produces the highest potassium of 0.3764% on the 21st day